2020
DOI: 10.3390/nu12061791
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Australia’s Health Star Rating System 2014–2019

Abstract: In June 2014, Australia and New Zealand adopted a voluntary front-of-pack nutrition label, the Health Star Rating (HSR) system. Our aim was to assess its uptake in Australia in the five years following adoption and examine the feasibility of proposed targets for future uptake. Numbers and proportions of products eligible to carry a HSR were recorded each year between 2014 and 2019 as part of an annual survey of four large Australian retail outlets. Uptake was projected to 2024. Mean HSR values were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…As the HSR system is currently voluntary, manufacturers can selectively apply the HSR to products receiving higher ratings. For example, Shahid et al reported that for a number of manufacturers, there was a 1.9 to 2.5-star difference between mean HSR displayed on their products compared with their other products that did not display the HSR [23]. This is also supported by the finding that just over three-quarters of products in this study had an HSR ≥ 2.5 stars with a median across the whole sample at an HSR of 3.5 stars.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As the HSR system is currently voluntary, manufacturers can selectively apply the HSR to products receiving higher ratings. For example, Shahid et al reported that for a number of manufacturers, there was a 1.9 to 2.5-star difference between mean HSR displayed on their products compared with their other products that did not display the HSR [23]. This is also supported by the finding that just over three-quarters of products in this study had an HSR ≥ 2.5 stars with a median across the whole sample at an HSR of 3.5 stars.…”
Section: Discussionsupporting
confidence: 76%
“…If the HSR was classifying foods correctly on the basis of ED, then we would expect a much lower percentage of high ED foods displaying a high HSR. This further adds to the body of literature, demonstrating the shortcomings of the HSR system [23,37,38,[40][41][42][43], and shows that it does not consistently discriminate between levels of ED, especially when considering high ED foods. The median ED of products with a high HSR was 1507 kJ/100 g, well above the cut-off (950 kJ/100 g), signifying the beginning of the high ED range [31].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In New Zealand In 2016, 2 years after adoption of the HSR, 5.3% of packaged food and beverage products surveyed (n = 807/15,357) displayed HSR labels [6]. In Australia, 5 years after adoption of the HSR, it can be found on 40.7% of food products [7]. Similarly as in our study, where about three-quarters of products displaying Nutri-Score were A, B or C, in Australia more than three quarters (76.4%) of products displaying HSR had a HSR ≥ 3.0.…”
Section: Uptake Of Nutri-score In Belgium In the First Year Of Implemmentioning
confidence: 99%